Dielectric ceramic composition and multilayer ceramic capacitor containing the same
By adopting an alkaline iron niobium-based dielectric ceramic composition, including perovskite structure and doped rare earths, transition metals and glass materials, the problem of unstable capacitance performance in high temperature environments is solved, and stable capacitance performance and high dielectric constants are achieved in a wide temperature range.
Patent Information
- Application Number
- CN202280008323.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-28
- Filing Date
- 2022-01-27
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-01-27
AI Technical Summary
Existing multi-layer ceramic capacitors cannot maintain stable capacitance performance under high temperature environments, especially in the temperature range of 175°C-200°C or higher.
An alkaline iron niobium-based dielectric ceramic composition is employed, which comprises the main component of the perovskite structure ABO3, and doped packaging of rare earth elements, transition metal elements and glass materials. The composition can be co-fired with the base metal inner electrode in a reducing atmosphere to form a multilayer ceramic capacitor suitable for high temperature applications.
The stability of the capacitance temperature coefficient within ±50% in the temperature range of -55°C to 200°C is achieved, and the dielectric constant at 25°C reaches at least 300, meeting the capacitance requirements in high temperature environments.
Smart Images

Figure BDA0004292245930000141 
Figure HDA0004292245940000011
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to pending U.S. provisional application No. 63 / 142,766, filed on January 28, 2021, which is incorporated herein by reference. Technical Field
[0003] The present invention relates to a dielectric ceramic composition and a multilayer ceramic capacitor containing the composition. The disclosed dielectric ceramic composition can be co-fired with a base metal inner electrode in a reducing atmosphere. The multilayer ceramic capacitor made therefrom is advantageous for use in high temperature applications. Background Art
[0004] With the rapid development and popularization of information and electronic technology in the past two decades, the multilayer ceramic capacitor industry has flourished due to the growing demand for electrical energy storage devices in numerous applications such as portable electronic devices, personal computers, mobile phones, televisions, etc. In these cases, due to the rapid development and popularization of information and electronic technology in the past two decades, the multilayer ceramic capacitor industry has flourished due to the growing demand for electrical energy storage devices in numerous applications such as portable electronic devices, personal computers, mobile phones, televisions, etc. 3 BaTiO is widely used as a basic ceramic dielectric material due to its high dielectric constant, low dielectric loss, and stable capacitance change in the temperature range of -55°C to 125°C. However, as a ferroelectric material, BaTiO 3 At around 125°C, it undergoes the well-known Curie transition, resulting in a significant decrease in the dielectric constant and a sudden drop in the temperature coefficient of capacitance. Today, with the emergence of new electronic applications in extreme environments, such as engine control units, downhole drilling, pulsed power electronics, etc., it is required to maintain stable capacitance within the maximum operating temperature window of 175°C-200°C or even higher. Although a lot of research activities have been carried out to stabilize BaTiO through extensive doping modification packages, 3 The temperature-capacitance characteristics of base capacitors are improved, but the extended operating temperature is still limited to about 150°C. Therefore, the development of new dielectric materials that can be used in harsh environments at 175°C-200°C or higher has attracted great attention. Among various candidate materials, basic niobate-based ceramics are found to be feasible for the development of high-temperature capacitors due to their high Curie transition temperature. For example, in (K 0.5 Na 0.5 )NbO 3In ceramics, this Curie transition occurs at around 410°C. Detailed firing studies and defect chemistry studies have shown that alkaline niobate-based ceramics can: (1) be co-fired with base metals (such as copper and nickel) in a reducing atmosphere due to carefully designed chemical thermodynamics that mitigate the volatility of the alkaline elements; and (2) produce multilayer structured electronic devices with base metal internal electrodes. For example, in U.S. Patent No. 9,564,271 and WO 2018 / 062084A1, (K,Na)NbO 3 Base dielectric ceramic composition and NaNbO 3 The base dielectric ceramic composition forms a layered ceramic capacitor condenser with Ni inner electrodes.
[0005] Despite significant efforts, there remains a need for improved ceramic dielectrics, particularly those suitable for use in multilayer ceramic capacitors and suitable for use at high voltages and temperatures. Summary of the invention
[0006] A dielectric ceramic is provided herein that is particularly suitable for use at high temperatures.
[0007] Also provided herein is a multilayer ceramic capacitor including a dielectric ceramic, wherein the capacitor is suitable for use at high temperatures.
[0008] These and other advantages are achieved in a dielectric ceramic composition comprising:
[0009] The principal components are defined by:
[0010] (K x Na y Li z A 1-x-y-z ) m (Nb u Ta v B w ) 3
[0011] in:
[0012] A is at least one element selected from Ca, Sr and Ba;
[0013] B is at least one element selected from Ti, Zr, Hf and Sn;
[0014] x, y, z, u, v, and w are the mole fractions of each element;
[0015] m is the molar ratio of the A-site element to the B-site element;
[0016] 0.95≤m≤1.05;
[0017] 0.05≤x≤0.90;
[0018] 0.05≤y≤0.90;
[0019] 0.00≤z≤0.12;
[0020] 0 <u<1;
[0021] 0.0≤w≤0.3; and
[0022] u+v+w=1;
[0023] a first subcomponent comprising at least one rare earth element selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu;
[0024] a second subcomponent comprising at least one transition metal element selected from the group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, and Zn; and
[0025] The third subcomponent includes frit.
[0026] Another embodiment provides a multilayer ceramic capacitor, comprising:
[0027] a plurality of dielectric ceramic layers, wherein each layer has a dielectric composition defined by;
[0028] (K x Na y Li z A 1-x-y-z ) m (Nb u Ta v B w ) 3
[0029] in:
[0030] A is at least one element selected from Ca, Sr and Ba;
[0031] B is at least one element selected from Ti, Zr, Hf and Sn;
[0032] x, y, z, u, v, and w are the mole fractions of each element;
[0033] m is the molar ratio of the A-site element to the B-site element;
[0034] 0.95≤m≤1.05;
[0035] 0.05≤x≤0.90;
[0036] 0.05≤y≤0.90;
[0037] 0.00≤z≤0.12;
[0038] 0 <u<1;
[0039] 0.0≤w≤0.3; and
[0040] u+v+w=1;
[0041] a first subcomponent comprising at least one rare earth element selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu;
[0042] a second subcomponent comprising at least one transition metal element selected from the group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; and
[0043] a third auxiliary component, the third auxiliary component comprising glass material;
[0044] and a plurality of internal electrodes comprising a base metal Ni, Cu or an alloy thereof;
[0045] and a pair of external electrodes formed at each end of the capacitor element body.
[0046] Another embodiment provides a method of forming a multilayer ceramic capacitor, comprising:
[0047] forming a dielectric ceramic precursor;
[0048] interlacing layers of the dielectric ceramic precursor with metal layers to form a stack;
[0049] Compressing the stack and sintering the dielectric precursor to form a dielectric ceramic layer having a composition defined by:
[0050] The principal component is defined as:
[0051] (K x Na y Li z A 1-x-y-z ) m (Nb u Ta v B w ) 3
[0052] in:
[0053] A is at least one element selected from Ca, Sr and Ba;
[0054] B is at least one element selected from Ti, Zr, Hf and Sn;
[0055] x, y, z, u, v, and w are the mole fractions of each element;
[0056] m is the molar ratio of the A-site element to the B-site element;
[0057] 0.95≤m≤1.05;
[0058] 0.05≤x≤0.90;
[0059] 0.05≤y≤0.90;
[0060] 0.00≤z≤0.12;
[0061] 0 <u<1;
[0062] 0.0≤w≤0.3; and
[0063] u+v+w=1;
[0064] a first subcomponent comprising at least one rare earth element selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu;
[0065] a second subcomponent comprising at least one transition metal element selected from the group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; and
[0066] The third subcomponent includes a glass frit. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 is a schematic cross-sectional view of a multilayer ceramic capacitor using the dielectric ceramic composition of the present invention. DETAILED DESCRIPTION
[0068] The present invention relates to a basic niobite-based dielectric ceramic composition having a further doping package of transition metals and rare earth elements. It is well known that doping or co-doping of transition metal elements and / or rare earth elements is beneficial to adjust the defect chemical landscape of the electroceramic material from a microstructural perspective, thereby controlling macroscopic electrical properties such as insulation resistance and long-term life reliability. The dielectric ceramic composition of the present invention can be co-fired with inexpensive electrodes mainly containing base metals under low oxygen partial pressure to produce multilayer ceramic capacitors that can be used for high temperature applications.
[0069] The present invention relates to a dielectric ceramic composition capable of achieving excellent temperature-capacitance characteristics from low temperature to high temperature. Specifically, the capacitance temperature coefficient of a capacitor made from the disclosed dielectric ceramic composition can be within ±50% in the temperature range of -55°C to 200°C, and more preferably within ±20% in the temperature range of -55°C to 200°C, relative to the capacitance at 25°C.
[0070] The dielectric ceramic composition has a dielectric constant of at least 300, more preferably at least 1000 and not more than 2000 at 25°C.
[0071] The present invention also relates to a dielectric ceramic composition which can be co-fired in a reducing atmosphere with an internal electrode using an inexpensive base metal such as Ni, etc.
[0072] The present invention also relates to a multilayer ceramic capacitor, which is formed by a plurality of stacked ceramic layers and a plurality of internal electrode layers in a manner that the ceramic layers and the internal electrode layers are alternately stacked. The ceramic layers are made of the dielectric ceramic composition of the present invention, and the internal electrode layers are made of a conductive paste mainly containing a base metal (such as nickel, etc.). The obtained multilayer ceramic capacitor can have a capacitance temperature coefficient within 15% in a temperature range of -55°C to 200°C after co-firing under low oxygen partial pressure.
[0073] The above object is achieved in a multilayer ceramic capacitor device comprising a dielectric ceramic composition having a main component having a perovskite structure ABO 3 , the molecular formula is:
[0074] (K x Na y Li z A 1-x-y-z ) m (Nb u Ta v B w ) 3
[0075] in:
[0076] A is at least one element selected from the alkaline earth element group consisting of Ca, Sr and Ba;
[0077] B is at least one element selected from Ti, Zr, Hf and Sn;
[0078] in:
[0079] x, y, z, u, v and w are the mole fractions of the elements, and m is the molar ratio of the A-site element to the B-site element;
[0080] 0.95≤m≤1.05;
[0081] 0.05≤x≤0.90;
[0082] 0.05≤y≤0.90;
[0083] 0≤z≤0.12;
[0084] 0 <u<1;0.0≤w≤0.3;u+v+w=1。
[0085] The ceramic composition further includes a first subcomponent comprising at least one element selected from rare earth compounds, wherein the rare earth element does not exceed 10 parts by mole relative to 100 parts by mole of the main component.
[0086] The ceramic composition further includes a second subcomponent including at least one element selected from transition metals, wherein the transition metal element is in a range of 0.05 parts by mole to 10.00 parts by mole relative to 100 parts by mole of the main component.
[0087] The ceramic composition further includes a third subcomponent including a compound having a low melting temperature (also referred to as frit) to assist the ceramic sintering process, the frit ranging from 0.01 to 15.00 parts by mole relative to 100 parts by mole of the main component.
[0088] In order to obtain the disclosed dielectric ceramic composition, (1) first, a precursor is prepared after calcination; the precursor here is defined as an intermediate compound or a group of compounds produced from certain raw ceramic powders, wherein the precursor may contain all or part of the constituent elements of the final composition, but the final form of the material is not obtained until the precursor is further mixed with other reactants and treated under certain thermal conditions to achieve the desired chemical composition; (2) then, before sintering, the obtained mixture of the precursor and other dopants (such as transition metal compounds, rare earth compounds and glass frits) is further prepared into a slurry form with the assistance of various organic blends; (3) finally, the composition containing the obtained slurry mixture forms the dielectric ceramic material disclosed in the present invention during the sintering process. An example is listed in Table 1. The precursor mainly comprises (K 0.5 Na 0.5 )NbO 3 -BaZrO 3 Ceramics, which are made of pre-reacted oxides and carbonates (such as K 2 CO 3 、Na 2 CO 3 、BaCO 3 , Nb 2 O 5 and ZrO 2 ), prepared by calcination. The inorganic dopant used to form the slurry before sintering is MnCO3 、Nd 2 O 3 and SiO 2 .
[0089] Table 1
[0090] Compounds used to form precursors <![CDATA[K 2 WHAT 3 ,On 2 WHAT 3 、BaCO 3 、Nb 2 ABOUT 5 、ZrO 2 ]]> Dopant <![CDATA[MnCO 3 、Nd 2 O 3 、SiO 2 ]]>
[0091] Dielectric ceramic materials can also be obtained by another route starting from more than one precursor (as exemplified in Table 2), using the same starting materials as in Table 1. In this case, two precursors, mainly Precursor 1 (K 0.5 Na 0.5 )NbO 3 and the precursor 2BaZrO 3 , respectively, by calcination. Then, by (K 0.5 Na 0.5 )NbO 3 、BaZrO 3 、MnCO 3 、Nd 2 O 3 and SiO 2 The blend of is formed into a slurry together with the organic mixture. After sintering, the formulation of Table 2 will produce a dielectric material composition that is substantially the same as the composition made by the formulation of Table 1.
[0092] Table 2
[0093] Compounds used to form precursor 1 <![CDATA[K 2 CO 3 、So 2 CO 3 、Nb 2 O 5 ]]> Compounds used to form precursor 2 <![CDATA[BaCO 3 、ZrO 2 ]]> Dopant <![CDATA[MnCO 3 、Nd 2 O 3 、SiO 2 ]]>
[0094] The present invention will be more fully described in the following examples, which are intended to illustrate, but not to limit the scope of the invention. However, these examples are merely representative of several of the various ways in which the principles of the invention may be employed.
[0095] The dielectric ceramic composition of the present invention comprises a main component and a subcomponent, wherein the main component has a perovskite structure ABO 3 , the molecular formula is:
[0096] (K x Na y Li z A 1-x-y-z ) m (Nb u Ta v B w ) 3 (1)
[0097] in:
[0098] A is at least one element selected from the alkaline earth element group consisting of Ca, Sr and Ba.
[0099] B is at least one element selected from the group consisting of Ti, Zr, Hf and Sn.
[0100] In formula (1), x, y, z, u, v and w are the molar fractions of the elements, and m is the molar ratio of the A-site element to the B-site element. The subscripts are respectively within the following ranges:
[0101] 0.95≤m≤1.05;
[0102] 0.05≤x≤0.90;
[0103] 0.05≤y≤0.90;
[0104] 0.00≤z≤0.12;
[0105] 0 <u<1;
[0106] 0.0≤w≤0.3; and
[0107] u+v+w=1.
[0108] The ceramic composition further includes a first auxiliary component, which includes at least one compound containing a rare earth element: Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu. The amount of the rare earth element does not exceed 10 mole parts relative to 100 mole parts of the main component. The mole fraction is based on YO 3 / 2 ScO 3 / 2 、LaO 3 / 2 、CeO 2 , PrO 11 / 6 、NdO 3 / 2 、SmO 3 / 2 ,EuO 3 / 2 , GdO 3 / 2 , TbO 7 / 4 , DyO 3 / 2 、HoO 3 / 2 , ErO 3 / 2 、TmO 3 / 2 , YbO 3 / 2 and LuO 3 / 2 Calculated based on.
[0109] The ceramic composition further includes a second subcomponent comprising at least one compound containing a transition metal element: V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; preferably, the compound contains at least one of V, Mo, W, Cr and Mn. The amount of the rare earth element is in the range of 0.05 to 10.00 parts by mole relative to 100 parts by mole of the main component.
[0110] The ceramic composition further includes a third subcomponent, which includes a compound having a low melting temperature (also referred to as a glass frit) to assist the ceramic sintering process, and at least one glass frit is selected from fluorides (such as LiF, NaF, KF and MgF 2 ), silicates (such as Si, SiO 2 and(Ba x Sr y Ca 1-x-y )SiO 3 (0≤x,y≤1)), borides (such as B 2 O 3 ) and oxides (such as Li 2 O、MoO 3 、V 2 O 5 The content of the glass frit is in the range of 0.01 mol parts to 15.00 mol parts relative to 100 mol parts of the main component.
[0111] To obtain Figure 1 The dielectric ceramic composition disclosed in the present application is used in the ceramic layer 2 of the multilayer ceramic capacitor 1 shown in the figure to prepare K 2 CO 3 、Na 2 CO 3 , Li 2 CO 3 、BaCO 3 、SrCO 3 、CaCO 3 、 2 O 5 , Nb 2 O 5 、TiO 2 、ZrO 2 , HfO 2 , transition metal oxides, rare earth oxides and glass frits are used as starting ceramic raw materials. In addition, as raw material compounds containing each component element in the dielectric formula disclosed in this application, not only oxides and carbonates but also hydroxides can be used. Specifically, the raw materials are not limited to any form. For example, transition metal elements (such as Mn) can be in the form of MnO, MnO 2 、MnCO 3 The main raw materials are weighed to meet the composition formula disclosed in the present application, and then wet mixed with a suitable solvent (such as water, ethanol, isopropanol, toluene, ethyl acetate, propyl acetate, butyl acetate, mineral solvent or other suitable hydrocarbon liquid or a blend thereof) through a yttrium-stabilized zirconium media ball mill. After drying and calcination, a ceramic material before sintering is obtained.
[0112] The calcined powder described herein is further wet-milled with the addition of water and / or suitable organic additives (such as binders, dispersants, solvents, plasticizers, etc.) to form a ceramic slip. There is no particular limitation on the choice of organic additives or organic content used herein.
[0113] In order to obtain the ceramic slurry described in this article and the ceramic composition disclosed below, the preparation steps are not limited to the above method, and can be adopted as follows: first, a precursor material is made by calcination, and then mixed with a precursor or dopant (containing other constituent elements of the desired composition), and then formed into a ceramic slurry with a suitable organic additive before sintering.
[0114] Examples 1 to 4 are given for illustration, but the description does not limit the scope of the present invention. Modifications obvious to those skilled in the art are all within the scope of the present invention.
[0115] Example 1
[0116] K 2 CO 3 、Na 2 CO 3 , Li 2 CO 3 、BaCO 3 、CaCO 3 、 2 O 5 , Nb 2 O 5 and ZrO 2 The starting ceramic raw materials are mixed and calcined at 700° C. to 1200° C. to prepare a precursor, wherein the starting ceramic raw materials include:
[0117] 30.7 mol% to 70.4 mol% from K 2 CO 3 K;
[0118] 29.5 mol% to 69.8 mol% from Na 2 CO 3 of Na;
[0119] 0.1 mol% to 10.1 mol% from Li 2 CO 3 Li;
[0120] 0.5 mol% to 12.5 mol% from BaCO 3 of Ba;
[0121] 0.1 mol% to 13.6 mol% from CaCO 3 Ca;
[0122] 0.05mol% to 27.70mol% from Ta 2 O 5 ;
[0123] 70.2mol% to 95.5mol% from Nb 2 O 5 Nb;
[0124] 0.1mol% to 23.1mol% from ZrO 2 Zr;
[0125] Then, a mixture of transition metal oxides, rare earth oxides and glass frits including the following is also added as a dopant together with suitable organic additives to form a ceramic slip:
[0126] 0.1mol% to 5.0mol% from MnCO 3 Mn;
[0127] 0.2 mol% to 4.9 mol% from Pr 6 O 11 Pr;
[0128] 0.01mol% to 5.30mol% from SiO 2 of glass material.
[0129] Example 2
[0130] K 2 CO 3 、Na 2 CO 3 , Li 2 CO 3 、BaCO 3 、SrCO 3 、CaCO 3 、 2 O 5 , Nb 2 O 5 、ZrO 2 and transition metal oxides (such as MnO and WO 3 ) as a starting ceramic raw material, and calcined at 700° C. to 1200° C. to prepare a precursor, wherein the starting ceramic raw material comprises:
[0131] 30.7 mol% to 70.4 mol% from K 2 CO 3 K;
[0132] 29.5 mol% to 69.8 mol% from Na2 CO 3 of Na;
[0133] 0.1 mol% to 10.1 mol% from Li 2 CO 3 Li;
[0134] 0.5 mol% to 12.5 mol% from BaCO 3 of Ba;
[0135] 0.3 mol% to 11.1 mol% from SrCO 3 Sr;
[0136] 0.1 mol% to 13.6 mol% from CaCO 3 Ca;
[0137] 0.05mol% to 27.70mol% from Ta 2 O 5 ;
[0138] 70.2mol% to 95.5mol% from Nb 2 O 5 Nb;
[0139] 0.1mol% to 23.1mol% from ZrO 2 Zr;
[0140] 0.1 mol% to 4.9 mol% Mn from MnO;
[0141] 0.1mol% to 2.2mol% from WO 3 W;
[0142] Then, a mixture of rare earth oxides and glass frits containing the following is also added as a dopant along with suitable organic additives to form a ceramic slip:
[0143] 0.2 mol% to 4.9 mol% from Y 2 O 3 Y;
[0144] 0.01mol% to 5.30mol% from CaSiO 3 of glass material.
[0145] Example 3
[0146] K 2 CO 3 、Na 2 CO 3 、BaCO3 、SrCO 3 、CaCO 3 , Nb 2 O 5 、ZrO 2 and rare earth oxides (such as Y 2 O 3 ) as a starting ceramic raw material, and calcined at 700° C. to 1200° C. to prepare a precursor, wherein the starting ceramic raw material comprises:
[0147] 30.7 mol% to 70.4 mol% from K 2 CO 3 K;
[0148] 29.5 mol% to 69.8 mol% from Na 2 CO 3 of Na;
[0149] 0.5 mol% to 12.5 mol% from BaCO 3 of Ba;
[0150] 0.3 mol% to 11.1 mol% from SrCO 3 Sr;
[0151] 0.1 mol% to 13.6 mol% from CaCO 3 Ca;
[0152] 70.2mol% to 95.5mol% from Nb 2 O 5 Nb;
[0153] 0.1mol% to 23.1mol% from ZrO 2 Zr;
[0154] 0.2 mol% to 4.9 mol% from Y 2 O 3 Y;
[0155] Then, a mixture of transition metal oxides and glass frits comprising the following is also added as a dopant along with suitable organic additives to form a ceramic slip:
[0156] 0.1mol% to 5.0mol% from MnO 2 Mn;
[0157] 0.01 mol% to 5.30 mol% of B 2 O 3 of glass material.
[0158] Example 4
[0159] K 2 CO 3 、Na 2 CO 3 、BaCO 3 、SrCO 3 、CaCO 3 、 2 O 5 , Nb 2 O 5 、TiO 2 、ZrO 2 , rare earth oxides (such as Nd 2 O 3 ) and a transition metal oxide (such as MnO) as starting ceramic raw materials are mixed and calcined at 700° C. to 1200° C. to prepare a precursor, wherein the starting ceramic raw materials include:
[0160] 30.7 mol% to 70.4 mol% from K 2 CO 3 K;
[0161] 29.5 mol% to 69.8 mol% from Na 2 CO 3 of Na;
[0162] 0.5 mol% to 12.5 mol% from BaCO 3 of Ba;
[0163] 0.3 mol% to 11.1 mol% from SrCO 3 Sr;
[0164] 0.1 mol% to 13.6 mol% from CaCO 3 Ca;
[0165] 0.05mol% to 27.70mol% from Ta 2 O 5 ;
[0166] 70.2mol% to 95.5mol% from Nb 2 O 5 Nb;
[0167] 0.05mol% to 4.70mol% from TiO 2 Ti;
[0168] 0.1mol% to 23.1mol% from ZrO 2 Zr;
[0169] 0.2mol% to 4.9mol% from Nd 2 O 3 La;
[0170] 0.1 mol% to 4.9 mol% Mn from MnO;
[0171] Then, 0.01 mol% to 5.30 mol% of frit LiF is also added as a dopant along with suitable organic additives to form a ceramic slip.
[0172] In addition, dopants such as transition metal compounds, rare earth compounds and glass materials can also be added in two separate steps to obtain the desired dielectric composition disclosed in the present invention. This means that a partial amount of transition metal compounds, rare earth compounds and / or glass materials are first added to the raw materials, and a precursor is prepared after calcination at 700°C to 1200°C, which is called step 1; then another amount of transition metal compounds, rare earth compounds and / or glass materials are further added to the precursor together with appropriate organic additives to form a ceramic slurry, which is called step 2. The transition metal compounds added in step 1 and step 2 can be the same compound containing the same target transition metal element, or different compounds containing different target transition metal elements. This also applies to rare earth compounds and glass materials if they are added separately in step 1 and step 2. The total amount of transition metal elements, rare earth elements and glass materials added in step 1 and step 2 satisfies the numerical range specified in formula (1).
[0173] Examples 5 to 10 are given for illustration, but the illustration does not limit the scope of the present invention. Modifications obvious to those skilled in the art are all within the scope of the present invention.
[0174] Example 5
[0175] K 2 CO 3 、Na 2 CO 3 、BaCO 3 、SrCO 3 、CaCO 3 , Nb 2 O 5 、ZrO 2 , HfO 2 and transition metal oxides (such as MoO 3 ) as a starting ceramic raw material, and calcined at 700° C. to 1200° C. to prepare a precursor, wherein the starting ceramic raw material comprises:
[0176] 30.7 mol% to 70.4 mol% from K 2 CO3 K;
[0177] 29.5 mol% to 69.8 mol% from Na 2 CO 3 of Na;
[0178] 0.5 mol% to 12.5 mol% from BaCO 3 of Ba;
[0179] 0.3 mol% to 11.1 mol% from SrCO 3 Sr;
[0180] 0.1 mol% to 13.6 mol% from CaCO 3 Ca;
[0181] 70.2mol% to 95.5mol% from Nb 2 O 5 Nb;
[0182] 0.1mol% to 19.7mol% from ZrO 2 Zr;
[0183] 0.1mol% to 5.4mol% from HfO 2 Hf;
[0184] 0.1mol% to 2.2mol% from MoO 3 Mo;
[0185] Then, a mixture of transition metal oxides, rare earth oxides and glass frits including the following is also added as a dopant together with suitable organic additives to form a ceramic slip:
[0186] 0.1mol% to 5.0mol% from MnO 2 Mn;
[0187] 0.2 mol% to 4.9 mol% from Dy 2 O 3 Dy;
[0188] 0.01 mol% to 5.30 mol% of the glass frit from LiF.
[0189] Example 6
[0190] K 2 CO 3 、Na 2 CO 3 、SrCO 3 、CaCO 3、 2 O 5 , Nb 2 O 5 、ZrO 2 , HfO 2 and rare earth oxides (such as Yb 2 O 3 ) as a starting ceramic raw material, and calcined at 700° C. to 1200° C. to prepare a precursor, wherein the starting ceramic raw material comprises:
[0191] 30.7 mol% to 70.4 mol% from K 2 CO 3 K;
[0192] 29.5 mol% to 69.8 mol% from Na 2 CO 3 of Na;
[0193] 0.3 mol% to 13.2 mol% from SrCO 3 Sr;
[0194] 0.1 mol% to 13.6 mol% from CaCO 3 Ca;
[0195] 0.05mol% to 27.70mol% from Ta 2 O 5 ;
[0196] 70.2mol% to 95.5mol% from Nb 2 O 5 Nb;
[0197] 0.1mol% to 19.7mol% from ZrO 2 Zr;
[0198] 0.1mol% to 5.4mol% from HfO 2 Hf;
[0199] 0.2 mol% to 1.8 mol% from Yb 2 O 3 Yb;
[0200] Then, a mixture of transition metal oxides, rare earth oxides and glass frits including the following is also added as a dopant together with suitable organic additives to form a ceramic slip:
[0201] 0.2mol% to 5.0mol% from CeO 2 Ce;
[0202] 0.1mol% to 4.9mol% from MnO 2 Mn;
[0203] 0.01mol% to 5.30mol% from CaSiO 3 of glass material.
[0204] Example 7
[0205] K 2 CO 3 、Na 2 CO 3 、BaCO 3 、SrCO 3 , Nb 2 O 5 、ZrO 2 and transition metal oxides (such as MnO 2 ) as a starting ceramic raw material, and calcined at 700° C. to 1200° C. to prepare a precursor, wherein the starting ceramic raw material comprises:
[0206] 30.7 mol% to 70.4 mol% from K 2 CO 3 K;
[0207] 29.5 mol% to 69.8 mol% from Na 2 CO 3 of Na;
[0208] 0.5 mol% to 12.5 mol% from BaCO 3 of Ba;
[0209] 0.3 mol% to 11.1 mol% from SrCO 3 Sr;
[0210] 70.2mol% to 95.5mol% from Nb 2 O 5 Nb;
[0211] 0.1mol% to 19.7mol% from ZrO 2 Zr;
[0212] 0.1mol% to 1.6mol% from MnO 2 Mn;
[0213] Then, a mixture of transition metal oxides, rare earth oxides and glass frits including the following is also added as a dopant together with suitable organic additives to form a ceramic slip:
[0214] 0.1mol% to 2.2mol% from MoO 3 Mo;
[0215] 0.2 mol% to 4.9 mol% from Y 2 O 3 Y;
[0216] 0.01 mol% to 5.30 mol% of glass frit from KF.
[0217] Example 8
[0218] K 2 CO 3 、Na 2 CO 3 , Li 2 CO 3 、SrCO 3 、CaCO 3 、 2 O 5 , Nb 2 O 5 、ZrO 2 , transition metal oxides (such as WO 3 ) and glass materials (such as SiO 2 ) as a starting ceramic raw material, and calcined at 700° C. to 1200° C. to prepare a precursor, wherein the starting ceramic raw material comprises:
[0219] 30.7 mol% to 70.4 mol% from K 2 CO 3 K;
[0220] 29.5 mol% to 69.8 mol% from Na 2 CO 3 of Na;
[0221] 0.1 mol% to 10.1 mol% from Li 2 CO 3 Li;
[0222] 0.3 mol% to 11.1 mol% from SrCO 3 Sr;
[0223] 0.1 mol% to 13.6 mol% from CaCO 3 Ca;
[0224] 0.05mol% to 27.70mol% from Ta 2 O 5 ;
[0225] 70.2mol% to 95.5mol% from Nb 2 O 5 Nb;
[0226] 0.1mol% to 23.1mol% from ZrO 2 Zr;
[0227] 0.1mol% to 2.2mol% from WO 3 W;
[0228] 0.01mol% to 2.20mol% from SiO 2 Glass material;
[0229] Then, a mixture of transition metal oxides, rare earth oxides and glass frits comprising the following is further added as a dopant together with a suitable organic additive to form a ceramic slip:
[0230] 0.1mol% to 5.0mol% from MnO 2 Mn;
[0231] 0.2 mol% to 4.9 mol% from Y 2 O 3 Y;
[0232] 0.01mol% to 5.30mol% from BaSiO 3 of glass material.
[0233] Example 9
[0234] K 2 CO 3 、Na 2 CO 3 、BaCO 3 、CaCO 3 , Nb 2 O 5 、ZrO 2 , transition metal oxides (such as MoO 3 ), rare earth oxides (such as Y 2 O 3 ) and glass materials (such as SiO 2 ) as a starting ceramic raw material, and calcined at 700° C. to 1200° C. to prepare a precursor, wherein the starting ceramic raw material comprises:
[0235] 30.7 mol% to 70.4 mol% from K 2 CO 3 K;
[0236] 29.5 mol% to 69.8 mol% from Na2 CO 3 of Na;
[0237] 0.5 mol% to 12.5 mol% from BaCO 3 of Ba;
[0238] 0.1 mol% to 13.6 mol% from CaCO 3 Ca;
[0239] 70.2mol% to 95.5mol% from Nb 2 O 5 Nb;
[0240] 0.1mol% to 19.7mol% from ZrO 2 Zr;
[0241] 0.1mol% to 2.2mol% from MoO 3 Mo;
[0242] 0.1 mol% to 1.5 mol% of Y 2 O 3 Y;
[0243] 0.01mol% to 2.20mol% from SiO 2 Glass material;
[0244] Then, a mixture of transition metal oxides, rare earth oxides and glass frits including the following is also added as a dopant together with suitable organic additives to form a ceramic slip:
[0245] 0.1mol% to 5.0mol% from MnO 2 Mn;
[0246] 0.2 mol% to 4.9 mol% from Y 2 O 3 Y;
[0247] 0.01mol% to 5.30mol% from CaSiO 3 of glass material.
[0248] Example 10
[0249] K 2 CO 3 、Na 2 CO 3 、BaCO 3 、SrCO 3 、CaCO 3 、 2 O5 , Nb 2 O 5 、ZrO 2 , HfO 2 and glass materials (such as SiO 2 ) as a starting ceramic raw material, and calcined at 700° C. to 1200° C. to prepare a precursor, wherein the starting ceramic raw material comprises:
[0250] 30.7 mol% to 70.4 mol% from K 2 CO 3 K;
[0251] 29.5 mol% to 69.8 mol% from Na 2 CO 3 of Na;
[0252] 0.5 mol% to 12.5 mol% from BaCO 3 of Ba;
[0253] 0.3 mol% to 11.1 mol% from SrCO 3 Sr;
[0254] 0.1 mol% to 13.6 mol% from CaCO 3 Ca;
[0255] 0.05mol% to 27.70mol% from Ta 2 O 5 ;
[0256] 70.2mol% to 95.5mol% from Nb 2 O 5 Nb;
[0257] 0.1mol% to 19.7mol% from ZrO 2 Zr;
[0258] 0.1mol% to 5.4mol% from HfO 2 Hf;
[0259] 0.01mol% to 2.20mol% from SiO 2 Glass material;
[0260] Then, a mixture of transition metal oxides, rare earth oxides and glass frits including the following is also added as a dopant together with suitable organic additives to form a ceramic slip:
[0261] 0.1mol% to 5.0mol% from MnO 2 Mn;
[0262] 0.1mol% to 3.4mol% from V 2 O 5 V;
[0263] 0.2 mol% to 4.9 mol% from Pr 6 O 11 Pr;
[0264] 0.01 mol% to 5.30 mol% of the glass frit from LiF.
[0265] Embodiment 11
[0266] K 2 CO 3 、Na 2 CO 3 、SrCO 3 , Nb 2 O 5 and ZrO 2 The starting ceramic raw materials are mixed and calcined at 700° C. to 1200° C. to prepare a precursor, wherein the starting ceramic raw materials include:
[0267] 30.7 mol% to 70.4 mol% from K 2 CO 3 K;
[0268] 29.5 mol% to 69.8 mol% from Na 2 CO 3 of Na;
[0269] 0.1 mol% to 15 mol% from SrCO 3 Sr;
[0270] 70.2mol% to 95.5mol% from Nb 2 O 5 Nb;
[0271] 0.1mol% to 23.1mol% from ZrO 2 Zr;
[0272] Then, a mixture of transition metal oxides, rare earth oxides and glass frits including the following is added as a dopant to the main component:
[0273] 0.1mol% to 5.0mol% from MnCO 3 Mn;
[0274] 0.2 mol% to 4.9 mol% from Eu 2 O3 of Eu;
[0275] 0.01mol% to 5.3mol% from SiO 2 of glass material.
[0276] Example 12 -Compare
[0277] K 2 CO 3 、Na 2 CO 3 、SrCO 3 , Nb 2 O 5 and ZrO 2 The starting ceramic raw materials are mixed and calcined at 700° C. to 1200° C. to prepare a precursor, wherein the starting ceramic raw materials include:
[0278] 30.7 mol% to 70.4 mol% from K 2 CO 3 K;
[0279] 29.5 mol% to 69.8 mol% from Na 2 CO 3 of Na;
[0280] 0.1 mol% to 11.7 mol% from SrCO 3 Sr;
[0281] 70.2mol% to 95.5mol% from Nb 2 O 5 Nb;
[0282] 0.1mol% to 13.5mol% from ZrO 2 Zr;
[0283] Then, a mixture of transition metal oxides, rare earth oxides and glass frits including the following is added as a dopant to the main component:
[0284] 0.1mol% to 5.0mol% from MnCO 3 Mn;
[0285] 0.1 mol% to 4.2 mol% from CaCO 3 Ca;
[0286] 0.2mol% to 2.5mol% from WO 3 W;
[0287] 0.01mol% to 3.3mol% from SiO2 of glass material.
[0288] Preparation of dielectric ceramic disk samples
[0289] The ceramic powders of the main component and the auxiliary component are weighed according to the proportions in the embodiment and wet mixed with a ball mill for 12 to 30 hours. Then, the blend is dried at 150°C for 1 to 8 hours. A binder solution is added to the mixture in the mortar, and then granulated to form particles. Then, the obtained particles are loaded into a steel mold with a diameter of 13 mm and pressed at a pressure of 200 MPa to form a disc compact. The obtained compact is calcined in air at a maximum temperature of 375°C for 10 to 100 hours to burn off the organic binder. Next, it is fired in a reducing atmosphere to obtain a sintered disc. The firing is carried out at a peak temperature of 900°C to 1350°C and kept warm for 1 to 6 hours. Then, silver electrodes are applied to both surfaces of the sintered body to obtain disc ceramic capacitors corresponding to Examples 11 and 12.
[0290] Preparation of MLCC samples
[0291] By sintering at a temperature range of 900° C. to 1350° C., a sintered MLCC sheet with a standard size of 3.2 mm×1.6 mm and nickel inner electrodes was obtained. The sintered MLCC sheet contained 19 active dielectric ceramic layers and 20 nickel electrodes. The average thickness of the dielectric ceramic layer was determined to be about 12 μm.
[0292] Electrical Measurements
[0293] The electrostatic capacitance and dielectric loss of each composition were measured at 1 kHz and AC1 V over a temperature range of -55°C to 200°C. The temperature coefficient of capacitance (TCC) was calculated according to the following formula:
[0294] TCC (%) = [(CT-C 25 ) / C 25 ]×100
[0295] Where T is the temperature at which the measurement is performed, C T and C 25 are the electrostatic capacitance at temperature T and 25°C respectively.
[0296] Table 3 shows a comparison of the dielectric properties of the disc samples with or without rare earth element addition.
[0297] Table 3
[0298]
[0299] The results shown in Table 3 illustrate the advantages of the inventive example 11 containing the rare earth element Eu over the comparative example 12. Even though both examples provided TCC within ±20%, the comparative example did not achieve a sufficient dielectric constant.
[0300] Table 4 provides the dielectric constant of the disc samples made from the formulation of Example 11 as a function of firing temperature.
[0301] Table 4
[0302] Firing temperature ℃ Dielectric constant at 25°C 1050℃ 394 1100℃ 536 1150℃ 619 1250℃ 1607
[0303] The results in Table 4 show that a wide range of dielectric constants can be obtained by varying the firing temperature.
[0304] The data shown in Table 5 illustrate a comparison of the dielectric properties of MLCC samples made from the formulations shown in Example 11 and Example 12.
[0305] Table 5
[0306] Dielectric constant at 25°C TCC in the range of -55°C to 200°C Embodiment 11 1143 -33.3% to -0.29% Example 12 550 -44.08% to -0.89%
[0307] The results shown in Table 5 indicate that rare earth addition can greatly increase the dielectric constant and narrow the TCC range.
[0308] Using the tape casting process, the slurry is further formed into a ceramic green sheet by applying it to a support film using a doctor blade method. After a suitable drying process, a conductive ink mainly containing a base metal (such as Ni, Cu or its alloy) is used to form a ceramic green sheet. Figure 1 The internal electrodes 3a and 3b shown are screen printed onto the ceramic green sheet. Preferably, Ni or an alloy consisting mainly of Ni is used.
[0309] The obtained ceramic green sheets are further processed into green chips by a stacking process. A plurality of ceramic green sheets without electrodes printed thereon are stacked as the bottom covering layer 4b; then, a plurality of ceramic green sheets with electrodes printed thereon are stacked in alternating directions to form alternating electrodes 3a and 3b terminated at opposite ends; finally, a certain number of ceramic green sheets without electrodes printed thereon are stacked as the top covering layer 4a. The laminate is then pressed between 20°C and 120°C to improve the adhesion of all stacked layers, and further cut into individual green chips.
[0310] The green sheet is heated to 200°C to 700°C in air or in a slightly reducing atmosphere for 0.1 to 100 hours to burn off the binder, and then heated to 900°C to 1350°C in an atmosphere with an oxygen partial pressure of 10 -4 atm to 10 -16After sintering, the sheet can be further subjected to a reoxidation step by 10 -3 atm to 10 -14 The mixture was heated to a temperature not exceeding 1100° C. under an oxygen partial pressure of 1.5 atm. Thus, a sintered sheet was obtained.
[0311] The sintered sheet is rounded by roller or sandblasting to expose the internal electrodes formed on the two end surfaces of the ceramic sintered body. Subsequently, the external electrodes 5a and 5b are formed on the two end surfaces in the following manner: (1) Copper terminals are formed by applying a suitable copper paste to the two end surfaces of the sintered sheet and baking them in nitrogen or a slightly reducing atmosphere at a temperature between 600°C and 1000°C for 1 minute to 60 minutes; (2) A nickel plating layer and a tin plating layer or other suitable solder composition are further plated on the copper terminals by a roller plating method to improve solderability and prevent oxidation of the copper external electrodes. Thus, a multilayer ceramic capacitor 1 formed of base metal electrodes 3a and 3b and a dielectric ceramic layer 2 comprising the dielectric composition disclosed in the present invention is obtained.
[0312] The present invention discloses a dielectric ceramic composition that can be used in high temperature applications. This ceramic formulation can be co-fired with a base metal electrode in a reducing atmosphere. Therefore, a multilayer ceramic capacitor can be produced using the dielectric ceramic composition disclosed in the present invention and a base metal internal electrode (such as Ni).
[0313] Ranges listed throughout the specification include all intermediate values with the same number of significant figures. As a non-limiting example, a range listed of 0.01 to 0.05 includes: 0.01, 0.02, 0.03, 0.04, and 0.05. If a range is listed with two numbers having different significant figures, the number with the smallest increment of significant figures determines the significant figures of both. As a non-limiting example, if a range is listed as 1.0 to 5, it is intended to refer to all numbers from 1.0 to 5.0.
[0314] The following documents are incorporated herein by reference: U.S. Patent No. 9,564,271, Banno et al.; WO2018-062084, Banno; JP2020-29375A, Takahashi et al.; Basemetal co-firedmultilayerpiezoelectrics, Gao et al., ActuatorsActuators, Vol. 5, No. 1, p. 8, 2016.
[0315] The present invention will be described with reference to the accompanying drawings, which are part of the specification provided for the purpose of clearly illustrating the present invention, but are not limiting. In each of the drawings, similar elements will be numbered accordingly. The present invention will be described with reference to preferred embodiments, but is not limited thereto. Other embodiments described and set forth in the appended claims will be realized by those skilled in the art.
Claims
1. A dielectric ceramic composition comprising The principal components are defined by: (K x So y Li z A 1-x-y-z ) m (Nb u Dad v B w )O3 in: A is at least one element selected from Ca, Sr and Ba; B is at least one element selected from Ti, Zr, Hf and Sn; x, y, z, u, v, and w are the mole fractions of each element; m is the molar ratio of the A-site element to the B-site element; 0.95≤m≤1.05; 0.05≤x≤0.90; 0.05≤y≤0.90; 0.00≤z≤0.03; 0<u<1; 0.0≤w≤0.3; and u+v+w=1; a first subcomponent, the first subcomponent comprising at least one rare earth element selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu; a second subcomponent, the second subcomponent comprising at least one transition metal element selected from the group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; and a third auxiliary component, wherein the third auxiliary component comprises glass material, The dielectric ceramic composition has a capacitance temperature coefficient of ±50% within a temperature range of -55°C to 200°C.
2. The dielectric ceramic composition according to claim 1, comprising not more than 10 mol% of the rare earth element relative to 100 mol% of the main component. 3 . The dielectric ceramic composition according to claim 1 , comprising 0.05 mol % to 10 mol % of the transition metal relative to 100 mol % of the main component. 4 . The dielectric ceramic composition according to claim 1 , comprising 0.01 mol % to 15.00 mol % of the glass frit relative to 100 mol % of the main component.
5. The dielectric ceramic composition according to claim 1, wherein the glass frit comprises a material selected from the group consisting of fluorides, silicates, borides, and oxides. 6 . The dielectric ceramic composition according to claim 1 , having a capacitance temperature coefficient of ±20% in a temperature range of −55° C. to 200° C.
7. The dielectric ceramic composition of claim 1, having a dielectric constant of at least 300 at 25°C.
8. The dielectric ceramic composition according to claim 7, having a dielectric constant of at least 1000 at 25°C.
9. A multilayer ceramic capacitor comprising: A plurality of dielectric ceramic layers, wherein each of said layers has a dielectric composition defined by: The principal components are defined as: (K x So y Li z A 1-x-y-z ) m (Nb u Dad v B w )O3 in: A is at least one element selected from Ca, Sr and Ba; B is at least one element selected from Ti, Zr, Hf and Sn; x, y, z, u, v, and w are the mole fractions of each element; m is the molar ratio of the A-site element to the B-site element; 0.95≤m≤1.05; 0.05≤x≤0.90; 0.05≤y≤0.90; 0.00≤z≤0.03; 0<u<1; 0.0≤w≤0.3; and u+v+w=1; a first subcomponent, the first subcomponent comprising at least one rare earth element selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu; a second subcomponent comprising at least one transition metal element selected from the group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; and a third auxiliary component, wherein the third auxiliary component comprises glass material; wherein the dielectric composition has a capacitance temperature coefficient of ±50% in the temperature range of -55°C to 200°C, and a plurality of internal electrodes comprising a base metal of Ni, Cu or an alloy thereof; and a pair of external electrodes formed at each end of the capacitor element body. 10 . The multilayer ceramic capacitor according to claim 9 , comprising not more than 10 mol % of the rare earth element relative to 100 mol % of the main component. 11 . The multilayer ceramic capacitor according to claim 9 , comprising 0.05 mol % to 10 mol % of the transition metal relative to 100 mol % of the main component. 12 . The multilayer ceramic capacitor according to claim 9 , comprising 0.01 mol % to 15.00 mol % of the glass frit relative to 100 mol % of the main component.
13. The multilayer ceramic capacitor of claim 9, wherein the glass frit comprises a material selected from the group consisting of fluorides, silicates, borides, and oxides.
14. The multilayer ceramic capacitor of claim 9, wherein the dielectric composition has a capacitance temperature coefficient of ±20% in a temperature range of -55°C to 200°C.
15. The multilayer ceramic capacitor of claim 9, wherein the dielectric composition has a dielectric constant of at least 300 at 25°C.
16. The multilayer ceramic capacitor of claim 15, wherein the dielectric composition has a dielectric constant of at least 1000 at 25°C.
17. A method of forming a multilayer ceramic capacitor, comprising: forming a dielectric ceramic precursor; interleaving layers of the dielectric ceramic precursor with metal layers to form a stack; Compressing the stack and sintering the material obtained after compressing the stack to form a dielectric ceramic layer, the dielectric ceramic layer having a dielectric composition defined by: The principal components are defined as: (K x So y Li z A 1-x-y-z ) m (Nb u Dad v B w )O3 in: A is at least one element selected from Ca, Sr and Ba; B is at least one element selected from Ti, Zr, Hf and Sn; x, y, z, u, v, and w are the mole fractions of each element; m is the molar ratio of the A-site element to the B-site element; 0.95≤m≤1.05; 0.05≤x≤0.90; 0.05≤y≤0.90; 0.00≤z≤0.03; 0<u<1; 0.0≤w≤0.3; and u+v+w=1; a first subcomponent, the first subcomponent comprising at least one rare earth element selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu; a second subcomponent comprising at least one transition metal element selected from the group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; and a third auxiliary component, wherein the third auxiliary component comprises glass material, The dielectric composition has a capacitance temperature coefficient of ±50% within a temperature range of -55°C to 200°C.
18. The method of forming a multilayer ceramic capacitor of claim 17, wherein the layer of dielectric ceramic precursor is prepared as a ceramic green body slurry comprising a mixture of an inorganic material and an organic additive, wherein the inorganic material comprises at least one combination of a precursor and a dopant.
19. The method of forming a multilayer ceramic capacitor of claim 18, further comprising sintering the ceramic green body slurry.
20. The method of forming a multilayer ceramic capacitor of claim 17, wherein the transition metal is selected from the group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, and Zn.
21. The method of forming a multilayer ceramic capacitor of claim 17, wherein the rare earth element is selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.
22. The method of forming a multilayer ceramic capacitor of claim 17, wherein the glass frit comprises at least one compound selected from the group consisting of fluorides, silicates, borides, and oxides.
23. The method of forming a multilayer ceramic capacitor according to claim 17, wherein the sintering is performed at a temperature of 900°C to 1350°C.
24. The method for forming a multilayer ceramic capacitor according to claim 17, wherein the sintering is performed at an oxygen partial pressure of 10 -16 atm to 10 -4 atm atmosphere.
25. The method of forming a multilayer ceramic capacitor according to claim 17, wherein the metal is a base metal Ni, Cu or an alloy thereof.
26. The method of forming a multilayer ceramic capacitor of claim 17, further comprising forming a pair of external electrodes at each end of the capacitor element body.
27. The method of forming a multilayer ceramic capacitor of claim 17, wherein the dielectric composition has a capacitance temperature coefficient of ±20% in a temperature range of -55°C to 200°C.
28. The method for forming a multilayer ceramic capacitor of claim 17 wherein the dielectric composition has a dielectric constant of at least 300 at 25°C.
29. The method of forming a multilayer ceramic capacitor of claim 28, wherein the dielectric composition has a dielectric constant of at least 1000 at 25°C.
Citation Information
Patent Citations
Dielectric composition and electronic component
JP2020029375A
Dielectric ceramic composition, stacked ceramic capacitor using the same, and method of manufacturing the same
US9564271B2
Dielectric ceramic composition, and ceramic capacitor
WO2018062084A1
Piezoelectric ceramic and piezoelectric device
CN103172374A
Unreduced dielectric ceramic material, process for producing the same, and layer-built ceramic capacitor
CN1287547A